2014
DOI: 10.1515/bjdm-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypodontia in the permanent dentition of Macedonian population

Abstract: Hypodontia or tooth agenesis is a condition at which the patient is missing one or more teeth due to a failure of those teeth to develop. This is not only an aesthetic, but also a functional deficiency. The incidence of congenitally missing teeth depends on etiological factors that affect tooth development, as well as which dentition is concerned, sex or race and geographic distribution. The tooth agenesis is mostly seen in teeth that are formed last in a given class (lateral incisors, second premolars and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
3
9
2
2
Order By: Relevance
“…Numerous studies have reported that tooth agenesis is more common in the mandible than in the maxilla (6,7,16,18), and these results were in agreement with our results. However, other studies have shown that the tooth agenesis was dominantly in the maxilla (8,15,17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have reported that tooth agenesis is more common in the mandible than in the maxilla (6,7,16,18), and these results were in agreement with our results. However, other studies have shown that the tooth agenesis was dominantly in the maxilla (8,15,17).…”
Section: Discussionsupporting
confidence: 93%
“…The reported prevalence of hypodontia, excluding the third molar, varies from 4.30% to 9.0% in the population of orthodontic patients (5,7,11,16,17) and from 1.11% to 11.01% in the population of other dental patients (3,4,6,8,12,18). The wide range of prevalence of hypodontia may be attributed to differences in sampling methods and sample size, as well as ethnic and racial differences.…”
Section: Discussionmentioning
confidence: 99%
“…to the most distal tooth in the group affecting second premolars and lateral incisors, as well as third molars [1]. Thus, these teeth are frequently affected by agenesis (4.28-7.52%) which is in accordance with our results [4][5][6][7]18]. A rare occurrence of oligodontia was reported in the Italian population (0.08%) which is in agreement with our result (0.09%) [24].…”
Section: Abnormalities Of Tooth Numbersupporting
confidence: 91%
“…Missing teeth were the most frequent abnormality of tooth number in the present sample of Serbian orthodontic patients (12.9%). The overall prevalence of missing teeth in recent studies was 0.027-21.6% [14,16,[18][19][20][21][22]. Such considerable differences in results could be explained by variation in sample composition and size, ethnicity and methodology.…”
Section: Abnormalities Of Tooth Numbermentioning
confidence: 99%
“…Oligodontia is termed as a rare developmental dental anomaly in humans characterised by the absence of six or more teeth, whereas hypodontia is defined as the developmental absence of one or more teeth excluding the third molars. It is one of the most common dental anomalies and has a negative impact on both esthetics and function (Acev and Gjorgova, 2014…”
Section: Introductionmentioning
confidence: 99%